Development of a self-care scale for women with polycystic ovary syndrome: a methodological approach - Kim, Miok (Frontiers in Public Health, 2025)
PurposeThis study aimed to develop and validate a scale to assess self-care practices in women with polycystic ovary syndrome (PCOS), guided by the middle-range theory of self-care for chronic illness.MethodsA methodological design was used. Items were generated through literature review and expert input. Content validity was evaluated by experts, and construct validity was tested using exploratory and confirmatory factor analyses (EFA and CFA). Internal consistency was assessed using Cronbach’s alpha. Data were collected from 453 women with PCOS in South Korea.ResultsThe final scale consisted of 18 items across five factors, explaining 59.3% of the total variance. Content validity was confirmed, and CFA indicated acceptable model fit. The scale demonstrated high internal consistency (Cronbach’s alpha = 0.90).ConclusionThis validated scale provides a reliable tool to measure self-care practices in women with PCOS, a common but often overlooked chronic condition. It can be used in clinical and public health settings to promote effective self-management, guide individualized care, and support the development of evidence-based interventions aimed at improving women’s health outcomes.